Indian Ephedras and their Supply - Singh, D. P. (Indian Forester, 1950)
Ephedras are the only source of Ehedrine Hydrochloride-a very important drug which is imported into the country after the main source of supply, viz., Baluchistan having gone over to Pakistan. The two important species of Ephedra generally met with are E. Gerardiana and E. Inlermedia and belong to the family Gnelaceae which is close allied to Conifer. In Lahau1 E. Gerardiana is the predominant species. The places where Ephedras grow are accessible and present little difficulty in collection. The cost of concentrated drug up to road head is likely to be Rs. 15 per maund and roughly about 40 tons of crude drug will be collected. It is of interest to note that a sample of Lahaul Ephedras has given 1.5% of pure Ephedrine, a very high percentage indeed.